Fordism: a review essay. (4th March 2019) - Watson, Daniel
ABSTRACT: Fordism is a central concept in American labour history. This essay, the first survey of the range of historiographical and sociological approaches deployed to understand Fordism, suggests that Fordism and Americanism are inseparably intertwined. Previous scholarship has emphasised that the technological and managerial efficiency of Fordist practice were a hallmark of twentieth-century Americanism. Historians of labour have demonstrated that these aspects manifested as a relentless system of control in the workplace that paradoxically helped to unify worker resistance. Historians of capitalism have tended to used Fordism to refer to an ethos underpinning mid-twentieth-century capitalist development marked by a balance between mass production and mass consumption. They identify increased social provisions and class compromise between labour and management as features that made Fordism attractive to states rebuilding their economies following the Second World War. New transnational histories of Fordism have begun to bridge the gap between these two main interpretations to show how Fordist practice and ethos were exported together internationally as part of an ideological project to modernise nations in America's image. This essay concludes by assessing the usefulness of Fordism to historians and suggesting avenues for future research.